PROTEKSI PIPA BAWAH LAUT DENGAN METODE ARTICULATED CONCRETE BLOCK MATTRESSES - Sulardi Sulardi (INFO-TEKNIK, 2020)
One of the problems in the operation of pipelines for oil and gas through the sea is the damage and failure submarine pipe line (SPL). The purpose of this study is to provide an overview of the factors and causes of damage and failure of the submarine pipeline which results in the cessation of the supply of feed intake of crude oil to the oil refinery unit. The method used in this research is a application research with a case study approach to the handling of problems with damage and failure of submarine pipelines, how the replacement and how to protect it is most suitable and in accordance with applicable regulations. The results showed that the protection of submarine pipelines with articulated concrete block matresses and immersion as deep as 2 meters had completed the regulatory aspects and were safe against the effects of collisions and dragged ship anchors. The results of this study also recommend that this protection method can be replicated to overcome similar problems in other work units.